A rare case of teenage adenoid cystic carcinoma of the breast (Indian Journal of Case Reports, 2017)
Adenoid cystic carcinoma (ACC) of the breast is very rare, accounting for only 0.1% of all breast carcinomas. Their rarity has made them difficult to study systematically with the most published series consisting of few cases or case reports; although, this existing evidence does suggest a good prognosis. ACC usually affects women, more in the sixth decade of life. However, our case has an exceptionally early onset of cancer at 16 years, the youngest ever reported in literature. Good local control can be obtained with lumpectomy and radiation or simple mastectomy for nearly all tumors. A routine axillary lymph node dissection is not recommended. We gave adjuvant radiotherapy to this patient in view of close margins and presence of lymphovascular emboli. She tolerated well with minimal side effects. Chemotherapy and hormonal therapy have no established benefit.